Roles of Human Respiratory Syncytial Virus Proteins in Immune Responses - Wang, Fengjie; Zhao, Linqing (Archives of Clinical and Biomedical Research, 2021)
Human respiratory syncytial virus (hRSV) has evaded active vaccination or effective antiviral therapy for decades and continues to be the leading cause of morbidity and hospitalization in infants, the elderly, and the immunocompromised worldwide. Inadequate understanding of the antigenic intricacies of its viral proteins and the immune responses they generate in the host is the greatest obstacle to the progress of hRSV prevention and treatment. Currently, the prefusion F protein is considered the most effective antigen for inducing protective immunity. Other molecular components of hRSV, such as the G or N proteins, have also been explored as potential targets for disease control. However, important knowledge gaps remain about the role played by various hRSV proteins in immunobiology and pathology. This review summarizes the unique immunomodulatory aspects of hRSV infection, the viral proteins involved in intracellular immune signaling, and the viral interactions in play with the host’s immune system.